Fluoro and pentafluorothio analogs of the antitumoral curcuminoid EF24 with superior antiangiogenic and vascular-disruptive effects. Issue 17 (1st September 2017) - Schmitt, Florian; Gold, Madeleine; Begemann, Gerrit; Andronache, Ion; Biersack, Bernhard; Schobert, Rainer
Graphical abstract: Highlights: Curcuminoids3 –6 are more cytotoxic than lead compound EF24 in cancer cells. Hexafluorinated piperidones3c and3d inhibit NF-κB translocation. Curcuminoids3c and4f inhibit angiogenesis in zebrafish embryos. Piperidones3c and3d are vascular-disrupting in CAM assays. Abstract: A series of 14 analogs of the curcuminoid EF24, (3 E, 5 E )-3, 5-bis[(2-fluorophenyl)methylene]-4-piperidinone, bearing fluorine or pentafluorothio substituents, were prepared and tested for antiproliferative, vascular-disruptive, and antiangiogenic activity, as well as for their influence on other cancer-relevant targets. They proved antiproliferative against eight cancer cell lines with IC50 values in the low single-digit micromolar to triple-digit nanomolar range. Like EF24, the hexafluoro3c and3d and bis(pentafluorothio)4f derivatives arrested HT-29 colon carcinoma cells in G2/M phase of the cell cycle, yet inhibited angiogenesis, e.g. in zebrafish larvae, to a much greater extent. The antimigratory effects in 518A2 melanoma cells of3c, its regioisomer3d, and of4f, originate from an inhibition of NF-κB translocation. Moreover, 3c and3d showed potential as vascular-disruptive agents in chorioallantoic/vitelline membrane (CA/VM) assays.